Temperament in obesity-related research: Concepts, challenges, and considerations for future research. (1st October 2019) - Stifter, Cynthia A.; Moding, Kameron J.
Abstract: Temperament, defined as individual differences in reactivity and regulation, has important implications for the development of childhood obesity. Indeed, numerous studies have demonstrated associations between temperament and children's eating behavior, parent feeding practices, and children's weight outcomes. Together, these findings have significantly improved our understanding of the developmental pathways to obesity-related outcomes. However, to better our understanding of the role of temperament in children's health, greater attention to how temperament is conceptualized and measured is needed. The purpose of this paper is to review the concept and principles of temperament, describe challenges in the measurement of temperament, and provide considerations for future research aimed at understanding the relationship between temperament, food intake, and childhood obesity. Moving forward, a fuller appreciation of the complexity of the temperament concept and thoughtful selection of temperament measures may help improve predictions and identify targets for interventions aimed at decreasing the risk for obesity in childhood.